Glass fiber reinforced composite resin space maintainer: case reports - (:unkn) unknown (My University, 2003)
PURPOSE: Glass fiber reinforced composite resins (GFRCR) are new to the pediatric dental market and can be an alternative to conventional space maintenainers. GFRCRs have been developed for dental applications during the past several years. This preliminary clinical study described the treatment of patients whose missing primary molars were restored with everStick, a semimanufactured product made of glass fibers, thermoplastic polymer, and lightcuring resin matrix for reinforcing dental polymer. METHODS: everStick was applied as a space maintainer when there was a loss of 1 or 2 teeth in the maxillary or mandibular arch. RESULTS: This study showed that the GFRCR space maintainers functioned well during a short period. The clinical advantages of the GFRCR space maintainers were that they: provided cost and time savings; did not require a cast model; did not require a second visit; were easy to apply; provided reliable adhesive bonding; provided long-term retention; were used when there was an indication of metal allergy; were easy to clean; had a natural feel and were esthetic. CONCLUSIONS: GFRCR space maintainers can be a new alternative to the conventional space maintainers used in pediatric dentistry.
Keywords: Humans; Child; Dental Materials; Orthodontic Appliances; Composite Resins; Orthodontic Appliance Design; Dental Bonding; Glass; Space Maintenance, Orthodontic